2018
DOI: 10.18553/jmcp.2018.24.6.494
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-Pocket Spending Not Associated with Oral Oncolytic Survival Benefit

Abstract: Background: With total and out-of-pocket spending for oral oncolytics rising, there is increased interest in choosing oncology treatments based on their clinical value relative to cost. Objectives: We sought to determine if out-of-pocket spending varied for higher versus lower benefit oral oncology drugs reimbursed by commercial insurers. Methods: This was a retrospective analysis of commercial insurer prescription drug claims filed between 2007–2014 for 13 oral oncolytics approved before 2009. We calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Due to the lack of patient-reported financial toxicity measures in all-claims databases [ 13 , 14 , 15 , 23 , 24 ] and SEER, we utilized NHIS to examine the association between medical care utilization and cancer type with patient-reported financial barriers and financial distress. We found that increased medical care utilization is associated with increased financial barriers, but no significant associations were seen with financial distress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the lack of patient-reported financial toxicity measures in all-claims databases [ 13 , 14 , 15 , 23 , 24 ] and SEER, we utilized NHIS to examine the association between medical care utilization and cancer type with patient-reported financial barriers and financial distress. We found that increased medical care utilization is associated with increased financial barriers, but no significant associations were seen with financial distress.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, financial toxicity is only incompletely assessed by using all-claims out-of-pocket copayment data, as these databases do not capture the extent of financial barriers experienced by the patient. Thus, studies utilizing these databases [ 13 , 14 , 15 ] provide an incomplete picture of financial toxicity. On the other hand, large national databases, such as the Surveillance, Epidemiology, and End Results Program (SEER) contain detailed cancer-specific diagnostic and treatment information but no care utilization or financial data.…”
Section: Introductionmentioning
confidence: 99%